Analisis Karakteristik Minyak Kedelai Dengan Penambahan Antioksidan Sebagai Alternatif Minyak Isolasi Transformator Terhadap Tegangan Tembus - Handayani, Yanolanda Suzantry; Rika Elvan; Irnanda Priyadi; Adhadi Kurniawan (UNIB Press, 2023)
With the addition of the antioxidant butylated hydroxyanisole (BHA) and phenol, it affects the breakdown voltage characteristics of soybean oil as an alternative to transformer insulating oil. This test varied the addition of BHA by 2%, 3%, and 4%, and variations in the addition of phenol by 2%, 3%, and 4%. Samples were prepared with a volume of 500 ml. Mixing soybean oil with BHA and PHENOLS by heating and stirring using a magnetic stirrer. The test was carried out using an AC high voltage ball butt system and the gap between the balls was 2 mm, 2.5 mm and 3 mm. From the results of this test, it was found that the average VBD of pure soybean oil was 8.0 kV at a ball spacing of 2.5 mm. but at a concentration of 2% BHA, the breakdown voltage value is 8.3 kV, an increase of 0.3 kV, from the average pure soybean oil. Whereas at a concentration of 3% there was a decrease of 0.9 kV, and at the addition of 2%, 3% and 4% phenolic concentrations it always increased steadily. The highest average breakdown voltage was found in the addition of 2% phenol of 30.8 kV or an increase of 22.8 kV from the average pure soybean oil. The average VBD of pure soybean oil which shows that the best antioxidant composition is obtained from 2% Phenol.